Automatic Exam Seating Generator: SmartSeat - R. Kanaka Raju; K. Sreeja; N.N.S. Francis; M. Revathi; Kalyan Patnaik (International Journal of Machine Systems and Manufacturing Technology, 2024)
The Automatic Exam Seating Arrangement System streamlines exam seating for institutions. It leverages algorithms to automate the tedious guide system. This avoids remaining minute rushes and confusion in locating the right venue. The device provides an application for admins and college students with examination timetables, timing and batch details to successfully control the seating process. Admins input parameters like student numbers and seating potential. Intelligent algorithms generate the greatest plans thinking about proximity and performance, The app automatically generates seat preparations for every student and messages them exam info. It’s working is controlled by an admin and advanced as a Java web application to streamline exam coordination. An automated examination hall seating app simplifies allotment and arrangement. Overall, it guarantees equity, prevents dishonesty, and eases admin burden. The paper ambitions to reduce the huge mission of manually allocating examination seats. The device dynamically allocates college students for efficiency. The prepared device routinely locations college students in favored spots. The workload is excessive in institutions but efficiency is low. This software saves enough time during exams with speedy, reliable overall performance.
Keywords: Automatic; Java; android app; android studio; arrangement; exam seating; examination hall